Assessing the Level of Knowledge and Attitude of Dentists and Increasing Awareness About Child Abuse and Neglect - Eskibağlar, Büşra Karaağaç; Ayna, Buket (Harran Üniversitesi, 2023)
Objective: This study aims to assess the knowledge level and attitude of dentists in Turkey about child abuse and neglect (CAN) and to increase the awareness of dentists with the informative booklet issued at the end of the assessment. Methodology: An electronic survey consisting of three sections and 45 questions was taken to the dentists. The first section included the personal data of the dentists, the second section consisted of their level of knowledge about CAN, and the third section included the questions to assess their attitudes about CAN. Results: The dentists taking part in the study were asked 27 questions in order to assess their knowledge level about CAN, and the mean score was determined 20,51 (64%), while the maximum score the participants could get was 32. The mean values for knowledge level about CAN were found to be significantly higher for women than men, for university hospital employees than private clinic employees, for attending physicians than non-attending, for pediatric dentistry than oral diagnosis and radiology, periodontology, prosthodontics, orthodontics, and endodontics specialists, for those with undergraduate and postgraduate education than those without education, and finally for those having received postgraduate education in vocational continuing training than those educated in PhD/career education. Conclusion: Dentistry is of the utmost importance to detect, prevent, and report this issue. As can be realized in the results of our study, this issue is not addressed strongly enough. Therefore, it is suggested that CAN should be included in the dentistry undergraduate, career, and doctorate educations, as well as in the continuing vocational educations.
Keywords: Dentistry; Diş Hekimliği